Giving Effect Of Lavender Aromatherapy A Sense Of Depression In Patients Using The Instrument Covid-19 Hrs-A - vittria meilinda; Sherly Amelia (Institute of Computer Science (IOCS), 2022)
Entering 2 years of the pandemic in Indonesia has caused anxiety for positive confirmed patients. In the latest data in December 2021, there were 278 new cases with an average of 321 cases in 1 week. Feelings of depression are included in the pattern of anxiety and mental health problems if too much is felt by someone which results in psychological anomalies during the Covid-19 pandemic. Lavender oil is known to contain anti-inflammatory, anti-fungal, antiseptic, anti-bacterial and anti-depressantthat can help relax (propertiescarminativetherapy). The content of linalyl acetate and linalool (C10H18O) The purpose of this study was to determine the effect of giving lavender aromatherapy on feelings of depression in Covid-19 patients. Data collection was carried out by observation using the HRS-A (instrumentHamilton Rating Scale Anxiety). The research design in this study was a quasi-experimental design with a pre- and post-test without control design. The sample in this study was 20 people who were confirmed positive for Covid-19 in the work area of the Bukittinggi City Health Office. The results of research conducted on positive confirmed subjects before being given treatment got an HRS-A score of 55 and after being given treatment, a HRS-A score of 26 was obtained so that the difference was 29 very significant values in reducing feelings of depression in patients who were confirmed positive for COVID-19. It is hoped that this research can provide an overview to be used as an alternative in reducing feelings of depression.